(3GdghjI GdKbGajI h GdCSQI aj GdHjFI GdEJUGdjI GdLOjOI (B/s - (3TGhj, djdjGs ((3GdLRGFQ (B:s (3fhGUQj aj GdWHGYI h GdfTQ ,s, 2022)
(3MGhdfG ef NdGd UaMGJ gPG GdcJGH GdJZdZd aj NHGjG GdCSQI YGeI h GdCSQI GdLRGFQjI h fTjQ Gf GdJQGK GdTahj GdeJfGbd YHQ GdCdSfI cGf MGaR HLeY GaQGO GdGSQ NGUI GdLRGFQjI jhejG NGUI aj SgQGJ GdSeQ h GdOQOTI h GdPj jSeM ddfTjA HGcJSGH eYGQa Yf JQGFge GdeMdj ef NdGd SdSdI GdJaGYdGJ GdJj jMedgG gPG GdJQGK dcf ef GdJWhQ GdJcfhdhLj h GfJTGQ GdYhdeI GdJj ZjQJ ehGRjf Gdbhi h ZjQJ MJi efaj GdeaGgje GdLhgQjI dHYV GdeUWdMGJ cGghjI GdKbGajI Ydi GQV GdhGbY h cd eG JMedg ef eVGejf cGdJQGK h GdYGOGJ h GdJbGdjO h GdJGQjN GdeTJQc ddJMhd aj GdYUQ GdQbej Gdi ghjI GaJQGVjI JgOO GdcKjQ ef GdGMjGf ghjI GdGSQI GdKbGajI hcjGfgG MjK jbhe GdGaQGO GdeTcdhf ddeLJeY GdGaJQGVj HHfGA ghjI GaJQGVjI GdcJQhfjI NGUI Jchf aj HYV GdGMjGf eWGHbI ddhGbY h aj GMjGf cKjQI eRjaI h eSJYGQIs
(3HHdjhZQGajG (B: (3U(B134-144s
Keywords: (3GdHjFI GdEJUGdjI GdLOjOIs; (3GdCSQIs; (3GdghjI GdKbGajI s